The business case for DAM - Regli, Theresa (Henry Stewart Talks, 2010)
Improved collaboration & streamlined creative workflow, 3 dimensions to a business case, DAM applied scenarios, Types of DAM vendors, Typical DAM use cases, DAM library or photo archive, Basic brand management, Multilingual brand management, Marketing collateral production and distribution, Ad production, Iterative production, Periodicals production and distribution, Multiple format publication, Multi channel publishing, Catalog publishing, Product catalog management, Rights management, E-learning, Video review and approval, Short form video production, Broadcast video or audio production, What is a business case?, Making your own business case, Typical business drivers, Benefits and costs of DAM, How to document and calculate in DAM, Best practices in DAM